Thermal behavior, spectroscopic studies and free radical scavenging potential of some mefenamate trivalent lanthanides (Sm, Eu, Gd, Tb and Dy) - Campos, Francisco X. [UNESP]; Nascimento, André L.C.S. [UNESP]; Colman, Tiago A.D. [UNESP]; Gálico, Diogo A.; Carvalho, Ana C.S.; Caires, Flávio J. [UNESP]; Siqueira, Adriano B.; Ionashiro, Massao [UNESP] (Elsevier, 2017)
Lanthanide Mefenamate compounds were prepared in solid state. TG-DSC coupled to FTIR, elemental analysis, complexometry with EDTA, X-ray powder diffractometry, evaluation of scavenging free radical activity with DPPH (2,2-diphenyl-1-picryl-hydrazine), and a complete spectroscopic study in the ultraviolet, visible, near-, and middle-infrared regions were realized to obtain some physicochemical properties of the synthesized compounds. The thermal stability, minimum formula, thermal behavior and intermediate compounds were indicated by thermoanalytical results. Furthermore, vibrational spectroscopy data suggests that the complexes are binuclear and two modes of coordination are presented. The DR spectra could be reveal the presence of a large ligand-to-metal charge transfer band in the europium mefenamate. This compound also indicated the higher antioxidant activity with DPPH (77.03% at 200 μg L−1).
Keywords: DPPH; EGA; Lanthanides; Mefenamate; Spectroscopy; Thermal analysis